2015
DOI: 10.5152/npa.2015.7653
|View full text |Cite
|
Sign up to set email alerts
|

What are the Predictors of Death in Patients With Cranio-Cervical Artery Dissection?

Abstract: Severe disability at admission was a mortality predictor in both CAD and VAD. Although the initial severity of stroke is reportedly related to poor outcomes in patients with CCAD, it has not previously been directly identified as a predictor of mortality in patients with CAD or VAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…The vascular wall vulnerability is important in the pathophysiology of especially spontaneous cases. The association between the connective tissue disorders and dissections supports this knowledge 5 . In a study conducted with 65 cases, the skin biopsy was confirmed the connective tissue disease in 55% of cases 6 .…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The vascular wall vulnerability is important in the pathophysiology of especially spontaneous cases. The association between the connective tissue disorders and dissections supports this knowledge 5 . In a study conducted with 65 cases, the skin biopsy was confirmed the connective tissue disease in 55% of cases 6 .…”
Section: Introductionsupporting
confidence: 67%
“…The recurrence was more common in young patients and the prognosis is better in this group. When all dissections were considered, 88% of cases had completed recovery with early diagnosis and treatment and the mortality was seen in only 10% of the cases 5,16,17 . There was no mortality in our cases and the rate of total recovery was 89.7% which was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekitar 1,7% pasien yang mengalami diseksi arteri karotis akan mengalami stroke iskemik dalam waktu 12 minggu, dan seringkali muncul pada minggu kedua. [2][3][4][5] Pada pasien dengan diseksi arteri di servikal, kejadian stroke paling sering muncul akibat adanya emboli yang berasal dari trombus yang lepas pada arteri yang mengalami diseksi. Kemungkinan lain penyebab stroke pada diseksi arteri karotis adalah terjadinya infark pada daerah watershed yang muncul akibat hipoperfusi, walaupun kejadian ini sangatlah jarang.…”
Section: Pendahuluanunclassified